2015
DOI: 10.1007/s00167-015-3890-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in coronal alignment of the ankle joint after high tibial osteotomy

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 25 publications
(30 reference statements)
3
65
0
1
Order By: Relevance
“…1,2 However, inability of these joints to completely reorient themselves after knee realignment may predispose to foot or ankle symptoms. 1,2,5 We feel this may have predisposed to ankle and hindfoot symptoms in the symptomatic group in our study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…1,2 However, inability of these joints to completely reorient themselves after knee realignment may predispose to foot or ankle symptoms. 1,2,5 We feel this may have predisposed to ankle and hindfoot symptoms in the symptomatic group in our study.…”
Section: Discussionmentioning
confidence: 73%
“…Incidence of new-onset ankle or hindfoot problems following MOWHTO has not been previously reported. Choi et al 5 reported that ankle symptoms were affected by coronal alignment changes in the ankle after MOWHTO. However, their study also included patients with preexisting ankle pain.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al found that the change of KJLO was signi cantly less than that of anatomical geometry of the proximal tibia. This phenomenon can be explained by the compensation of the ankle joint [8,18]. However, the capacity of compensation differs among individuals [9,15,25], and currently there is no information about the maximum of the capacity for most of the patients undergoing MOWHTO.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative knee joint obliquity can be compensated by the ankle joint [8,[15][16][17][18]. The capacity of compensation was suggested to be determined by the mobility of the subtalar joint [17,19], which differs by individual.…”
Section: Introductionmentioning
confidence: 99%
“…Varus knee deformity of the OA knee tends to have valgus hindfoot, and vice versa. In some previous reports, the change in the alignment of the knee due to a surgical intervention, such as total knee arthroplasty (TKA) [ 2 , 3 , 5 ] or high tibial osteotomy, [ 6 ] affects the alignment of the hindfoot within a short time after the surgery. Meanwhile, in rheumatoid arthritis (RA), it is not evident whether the compensatory correlation of the angle of the knee and hindfoot which is observed in OA patients can be applied using the same theory.…”
Section: Introductionmentioning
confidence: 99%